Effectiveness of Validated Teaching-Learning Package in Projectile Motion for Grade 9 Science - Chester Ian Sotto Pineda (Pascasarjana, Mataram University, 2020)
This study tested the validity and effectiveness of the developed Teaching- Learning Package in Projectile Motion for Grade 9 Science. A Teacher's Guide, a Learner's Module, and a Computer- Aided Instructional (CAI) tool comprised the package. The CAI tool composed of interactive simulations was developed using Adobe Flash Professional CC 2015 software and Small Basic and utilized the Microsoft PowerPoint 2016 as the overall platform. Research and Development design was employed in the study. The assessment of the package was done in five categories: (1) objectives, (2) contents of the Teacher's Guide and Learner's Module; (3) content quality, (4) instructional quality, and (5) technical quality of CAI tool by the five Physics and two ICT teachers. General average ratings of 3.58 and 4.41 were obtained from the assessment of the modules and CAI tool, respectively. Thus, teaching materials possess very good qualities. It is observed that the improvement of students who learned with the use of Teaching- Learning Package is greater than the traditional approach using a textbook. It is recommended that the developed Teaching- Learning Package should be used in teaching Projectile Motion for Grade 9 Science in the K- 12 curriculum